Surface Functionalization of SBA-15 for Immobilization of Myoglobin - Miao, Hengmin; Li, Maosheng; Wang, Fang; Li, Jiao; Lin, Ying-Wu; Xu, Jiakun (Frontiers in Bioengineering and Biotechnology, 2022)
Mesoporous molecular sieve SBA-15 was sucessfully modified with 3-aminopropyltriethoxysilane (APTES) and 3-glycidyloxypropyltrimethoxysilane (GPTMS). The functionalized SBA-15 were characterized with Small-angle X-ray (SAXRD), thermogravimetric analysis (TG), N2 adsorption and Fourier transformed infrared spectrum (FT-IR). APTES functionalized SBA-15(named SBA-15-A) and GPTMS functionalized SBA-15(named SBA-15-G) were used to immobilize myoglobin (Mb). The loading amounts of Mb by SBA-15-A and SBA-15-G were 511.2 and 547.8 mg/g, whereas only 359.6 mg/g was achieved by SBA-15. Mb/SBA-15-G and Mb/SBA-15-A showed improved reusability compared to SBA-15, and 84.6% and 82.7% of the initial activity still retained for SBA-15-A and SBA-15-G immobilized Mb even after repeated use for 7 times. The Mb/SBA-15-A and Mb/SBA-15-G also exhibited improved thermal stability and storage stability.